A Community-partnered Approach to Social Network Data Collection for a Large and Partial Network. Issue 2 (May 2023) - Izenberg, Maxwell; Brown, Ryan; Siebert, Cora; Heinz, Ron; Rahmattalabi, Aida; Vayanos, Phebe
In the small town of Sitka, Alaska, frequent and often catastrophic landslides threaten residents. One challenge associated with disaster preparedness is access to timely and reliable risk information. As with many small but diverse towns, who or what is a trustworthy source of information is often contested. To help improve landslide communication in Sitka, we used a community-partnered approach to social network analysis to identify (1) potential key actors for landslide risk communication and (2) structural holes that may inhibit efficient and equitable communication. This short take describes how we built trust and developed adaptive data collection methods to build an approach that was acceptable and actionable for Sitka, Alaska. This approach could be useful to other researchers for conducting social network analysis to improve risk communication, particularly in rural and remote contexts.